ChemInform Abstract: Phase‐Selective Synthesis of Cu2ZnSnS4 Nanocrystals Using Different Sulfur Precursors. Issue 51 (23rd December 2014) - Li, Zhenggang; Lui, Alvic Lim Kar; Lam, Kwan Hang; Xi, Lifei; Lam, Yeng Ming
Abstract Kesterite Cu2ZnSnS4 nanoparticles, wurtzite Cu2ZnSnS4 nanoparticles, as well as Cu2ZnSnS4 particles with a mixture of both structures are prepared by hot injection of the sulfur source into an oleylamine (OA) solution of Cu(OAc)2, ZnCl2, and SnCl4 using elemental sulfur, 1‐dodecanethiol, and thioacetamide in OA as sulfur source, respectively (235 °C, 1 h).